The Effect of Mobile Learning Media Based on Ispring Suite on Students' Learning Outcomes in Mathematics - Evri Sariati Pakpahan; Waminton Rajagukguk (PT FORMOSA CENDEKIA GLOBAL, 2023)
The low mathematics learning outcomes of class XI students at SMA Negeri 10 Medan, and the not yet utilized mobile learning media based on observation became the background for this research. This research intended to show how mobile learning media based on the Ispring Suite affects students' learning outcomes in mathematics. This research took place at SMA Negeri 10 Medan. The type of research in this study is a quasi-experiment with a nonequivalent control group design. Pre-test and post-test data collection techniques in the form of 10-multiple-choice questions were used. This research's sample was drawn at random and included 30 students from XI MIA 1 (the experiment class) and XI MIA 2 (the control class). Data of this research were analyzed by using normality test, homogeneity test, and t-test. The data gathered with the help of SPSS is normal and homogeneous. The independent t-test findings show that is greater than (2,594 > 2,002) and the significance value is 0,000 < 0,05, such that is rejected and is accepted. So, there is a difference between the mean of student post-test learning outcomes with mobile learning media based on Ispring suite and conventional learning model. In other words, using mobile learning media based on the Ispring Suite has an effect on student mathematics learning outcomes. Additionally, with an average score of 88% in the very good category, results from student response surveys to mobile learning media based on the Ispring Suite for learning were positive. It is suggested that mobile learning media based on the Ispring Suite be used to increase students' mathematics outcomes.